2018
DOI: 10.1016/j.pedn.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Sleep Is Associated with Obesity and Excessive Screen Time Amongst Ten-Year-Old Children in Sweden

Abstract: School-age children who receive less sleep are more likely to be overweight and report excessive television and computer use. A strong and urgent need exists to highlight the importance of healthy sleep and media habits. It is challenging for pediatric nurses and school nurses to teach children and their families about healthy sleep and media habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
4
26
0
2
Order By: Relevance
“…Over the past century, sleep duration has decreased by 0.75 min nightly per year both in children and adolescents [ 30 ]. In our present study, we found that 32.8% of children had insufficient sleep (sleep duration <9 h/day), which was consistent with the findings of recent studies [ 10 , 19 ]. The prevalence of vitamin D (25(OH)D) insufficiency and deficiency in our study was a little lower than prevalence described in previous studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Over the past century, sleep duration has decreased by 0.75 min nightly per year both in children and adolescents [ 30 ]. In our present study, we found that 32.8% of children had insufficient sleep (sleep duration <9 h/day), which was consistent with the findings of recent studies [ 10 , 19 ]. The prevalence of vitamin D (25(OH)D) insufficiency and deficiency in our study was a little lower than prevalence described in previous studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Lack of sleep or short sleep duration may increase the risk of obesity, cardiovascular disease, diabetes mellitus, total mortality and other unhealthy conditions [ 3 , 4 , 5 , 6 ].Nowadays, insufficient sleep is a public health problem in children and adolescents worldwide [ 7 , 8 , 9 ]. A recent epidemiological study in Sweden found that roughly 40% of children (aged 10 years) had sleep duration of less than 9 h per day [ 10 ]. Our previous cross-sectional study also showed a similar result [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sleep disorders in students can have both physical and psychological effects; sleep deprivation affects cognitive performance throughout the week. Furthermore, it has been shown that people who are obese or overweight sleep an average of 16 minutes less per day than those of normal weight [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that roughly 40% of school-aged children are not getting enough sleep [ 20 ]. A recent cross-sectional study in Sweden indicated that approximately 40% of children (aged 10 years) had sleep duration of less than 9 h per day [ 21 ]. Similarly, our previous epidemiological study also found that roughly 40% of sampled adolescents had a sleep duration of less than 8 h per day in Ningbo, Zhejiang province, China [ 22 ].…”
Section: Introductionmentioning
confidence: 99%